Stakeholder Perceptions of Sustainable Transportation in Bali Tourism - Mananda, I Gusti Putu Bagus Sasrawan; Wiratma, I Nyoman Adi; Sarjana, I Made Bram; Stiti, Ida Ayu Putu Santhi (Manunggal Halim Jaya, 2025)
Tourism in Bali, particularly in Badung Regency, drives significant economic growth but also creates challenges related to traffic congestion, greenhouse gas emissions, and environmental sustainability. Sustainable transportation has been identified as a key component of sustainable tourism, yet its implementation and stakeholder perceptions remain underexplored. This exploratory study employed a mixed-methods design, combining a survey of 50 stakeholders (tourists, residents, businesses, and government/NGO representatives) with semi-structured interviews. Quantitative analysis included descriptive statistics, correlation, and regression tests, while qualitative data provided contextual insights. Stakeholders perceived the availability (M = 3.12) and accessibility (M = 3.20) of sustainable transportation as moderate, with higher ratings from businesses and government compared to residents and tourists. Policy support (β = .34, p = .009) and business investment (β = .29, p = .021) emerged as significant enabling factors, while infrastructure limitations (β = –.31, p = .014) and high costs (β = –.28, p = .027) were the most critical constraints. Stakeholders recognized contributions of sustainable transport to competitiveness, particularly in enhancing environmental quality (M = 3.92) and reducing congestion (M = 3.74). The results suggest that while sustainable transportation initiatives exist, their reach remains uneven. Strong policy frameworks and private sector leadership are essential enablers, but adoption is hindered by infrastructure gaps and financial barriers. Stakeholders nevertheless view sustainable transport as central to Bali’s environmental sustainability and long-term competitiveness in the global tourism market.